A Study on the Digital Transformation Trends in Financial Management for Small and Micro Enterprises - Jiang, Jie (International Journal of Global Economics and Management, 2024)
This paper explores the impact of digital transformation trends on the financial management practices of small and micro enterprises (SMEs). It delves into the profound effects these trends have had on how SMEs handle their finances, from enhanced efficiency and transparency to new opportunities and challenges posed by technological advancements. The paper discusses how digital transformation has revolutionized the way SMEs collect, store, and analyze financial data, and how it has increased the transparency of SMEs’ financial operations. It also highlights how the application of digital technologies in financial management has opened up new avenues for SMEs to access financing and facilitated their integration into the global economy. However, the paper also acknowledges the challenges that come with the digital transformation of financial management in SMEs, such as data security concerns and the cost of adopting and maintaining digital financial management systems. Despite these challenges, the paper concludes that the overall impact of digital transformation on SME financial management has been overwhelmingly positive. It also discusses the significant impact of digital transformation on the way SMEs conduct their financial planning and budgeting. The paper further explores the various applications of digital technologies in the financial management of SMEs, focusing on areas such as automation, data analytics, cloud computing, blockchain, and artificial intelligence. It emphasizes the importance of integrating these technologies to create a comprehensive financial management system that is both efficient and effective. Finally, the paper explores the primary challenges encountered during digital transformation and outlines effective strategies for advancing this process in SMEs. It concludes that by adopting cost-effective solutions, seeking external expertise, fostering a culture of change, and prioritizing data standardization, SMEs can successfully navigate this transformation and reap the benefits of increased efficiency, transparency, and competitiveness.